2019
DOI: 10.1080/07350015.2019.1668798
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Impact of Global, Region-Specific, and Country-Specific Uncertainty

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 37 publications
5
56
0
Order By: Relevance
“…A growing consensus is that uncertainty actually arises as an endogenous response to other macroeconomic forces, such as specific aggregate demand or aggregate supply shocks, thus contributing to amplifying their effects (Mumtaz and Musso, 2019;Ludvigson et al, forthcoming). Given this, a question of paramount importance for policymakers is to determine the possible factors that can drive uncertainty, would allow policy authorities to determine in which direction the macroeconomy and financial markets are headed, and accordingly decide on the appropriate policy response.…”
Section: Introductionmentioning
confidence: 99%
“…A growing consensus is that uncertainty actually arises as an endogenous response to other macroeconomic forces, such as specific aggregate demand or aggregate supply shocks, thus contributing to amplifying their effects (Mumtaz and Musso, 2019;Ludvigson et al, forthcoming). Given this, a question of paramount importance for policymakers is to determine the possible factors that can drive uncertainty, would allow policy authorities to determine in which direction the macroeconomy and financial markets are headed, and accordingly decide on the appropriate policy response.…”
Section: Introductionmentioning
confidence: 99%
“…In a seminal paper, Jurado, Ludvigson and Ng (2015) measure uncertainty in the United States through a factor-augmented vector autoregression, using a large dataset of monthly macro and financial indicators. Berger, Grabert andKempa (2016, 2017), Mumtaz and Theodoridis (2017) and Mumtaz and Musso (2019) use multi-country factor models with stochastic volatility to decompose uncertainty in OECD countries into common and country-specific components. Using U.S. data, Carriero, Clark and Marcellino (2017) jointly estimate uncertainty and its impact on the economy through a large VAR in which stochastic volatility is driven by common factors.…”
Section: Introductionmentioning
confidence: 99%
“…First, to our knowledge this is the first paper that provides measures of global macroeconomic uncertainty and global spillovers of uncertainty using a GVAR model. Among the existing approaches for measuring international uncertainty, Mumtaz and Theodoridis (2017) Bloom and Furceri (2018) construct an index of uncertainty for 143 individual countries using the frequency of the word "uncertainty" in the quarterly Economist Intelligence Unit country reports. Rossi and Sekhposyan (2017) investigate spillovers of output growth-and inflation-based uncertainty using survey data for the Euro Area, while Klößner and Sekkel (2014) estimate spillovers of policy uncertainty among six developed countries using the EPU index by Baker et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mumtaz and Thedoridis (2017) decomposed the volatility of real economic activity, inflation, and other financial series for 11 OECD countries into the contribution from country-specific uncertainty and the contribution common to all OECD countries under study. In the same context, Mumtaz and Musso (2018) disentangled the variance of a wide set of macroeconomic and financial variables for 22 OECD countries into contributions from country-specific uncertainty, region-specific uncertainty, and global uncertainty. They found that all uncertainty estimates play a significant role in explaining the volatility of real economic activity, inflation, interest rates, stock prices, and exchange rates for most countries, but as time passes, the effect of common uncertainty is becoming stronger.…”
mentioning
confidence: 99%